2012
DOI: 10.1590/s0103-21002012000500021
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e funcionalidade da rede de apoio social do adulto com câncer

Abstract: Objective: To characterize the social support network of adults with cancer. Methods: A quantitative, exploratory, descriptive, cross-sectional research study conducted with adults with cancer, between August-November 2010, in their homes, using the Convoy of Social Support, and analysis of data with Microsoft Excel 2003. Results: Sixty-nine patients were consulted and cited 506 members in their support networks, aged 1 to 89 years, the majority being female, residing within 30 minutes of the patient's home an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
32

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 21 publications
2
15
0
32
Order By: Relevance
“…The literature review showed that there are few studies on the association between the SSN and HRQOL of chronic patients 17,19,22 . Moreover, there are no known studies about this field in MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review showed that there are few studies on the association between the SSN and HRQOL of chronic patients 17,19,22 . Moreover, there are no known studies about this field in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that participation in supporting groups for patients with MS was strongly linked to decreased anxiety and increased satisfaction with life 21 , and supporting a person with MS had an impact on the lives of informal caregivers 28 . One explanation for the low frequency of this type of analysis may be linked to the fact that the concept of a SSN is poorly defined, due to the heterogeneity in the analysis of its dimensions held by investigators, and it sometimes is confused with other close concepts, such as social support 17,29 . This theoretical obstacle requires the construction of network measurement scales of social support, systematizing .…”
Section: Discussionmentioning
confidence: 99%
“…Mostra-nos a literatura que tal evidencia deve-se ao fato de que a pessoa que vivencia uma condição crônica, como a deficiência física, requer atenção constante ao menos em alguma fase de sua vida, incumbindo à família, principalmente a nuclear, de suprir as demandas de seu cuidado (13). Apesar desta constatação, muitas vezes, a ocorrência da deficiência na família pode causar situações de crise no ambiente familiar, abalando sua estrutura e funcionamento, quando esta se vê despreparada para lidar com a nova condição de seu ente.…”
Section: Discussão E Conclusõesunclassified
“…Evidenciou-se o apoio advindo das relações de amizade, de vizinhos, de grupos, organizações e das relações de trabalho, que se interligam e complementam o apoio familial. Estes, no âmbito das relações mais íntimas, desenvolvem o papel de cuidadores informais, dando suporte emocional e amparo para que a pessoa com deficiência se beneficie, sendo mais autônoma e independente (13).…”
Section: Discussão E Conclusõesunclassified
See 1 more Smart Citation